1990
DOI: 10.1152/ajpheart.1990.258.5.h1274
|View full text |Cite
|
Sign up to set email alerts
|

Energy substrate utilization by isolated working hearts from newborn rabbits

Abstract: The ability of newborn rabbit hearts to utilize fatty acids as an energy substrate was determined. Isolated working hearts from 1- or 7-day-old rabbits were perfused with Krebs-Henseleit buffer containing either 11 mM glucose or 0.4 mM palmitate as carbon substrates. One-day-old rabbit hearts were perfused at a 11.5-mmHg filling pressure via the inferior vena cava and at a combined aortic and pulmonary arterial hydrostatic afterload of 20 mmHg. In these hearts, addition of insulin was necessary to maintain mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 0 publications
3
81
0
Order By: Relevance
“…Changes in ACC activity have been demonstrated to contribute to the maturation of fatty acid oxidation in hearts obtained from both newborn rabbits (1 and 7 d of age) (9,17,28), as well as hearts obtained from newborn pigs (14 d of age) (9,17,28). As we did not observe any age-dependent alteration in the phosphorylation of ACC (indicative of ACC inhibition), the data in this study suggests that in the newborn human heart the synthesis of malonyl CoA and maturation of fatty acid oxidation is not regulated by ACC activity, but is rather regulated by the extent of ACC expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in ACC activity have been demonstrated to contribute to the maturation of fatty acid oxidation in hearts obtained from both newborn rabbits (1 and 7 d of age) (9,17,28), as well as hearts obtained from newborn pigs (14 d of age) (9,17,28). As we did not observe any age-dependent alteration in the phosphorylation of ACC (indicative of ACC inhibition), the data in this study suggests that in the newborn human heart the synthesis of malonyl CoA and maturation of fatty acid oxidation is not regulated by ACC activity, but is rather regulated by the extent of ACC expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although plasma fatty acid levels rapidly rise to levels seen in the adult immediately after birth (6), newborn rabbit studies have shown that the heart undergoes a transition from oxidizing glucose to oxidizing fatty acids during the 7 d immediately after birth (9,10). The time frame responsible for the maturation of fatty acid oxidation in the human newborn heart is not yet known.…”
mentioning
confidence: 99%
“…Pioneering work by multiple groups has defined dynamic shifts in fuel utilization capacity and preferences during development and in disease states. The fetal and immediate postnatal heart relies primarily on glucose (glycolysis) and lactate as energy sources (3)(4)(5). However, very soon after birth the heart shifts to fatty acids as the major fuel substrate, coincident with the mitochondrial biogenic response (Figure 1 and refs.…”
Section: Brief Overview Of Cardiac Fuel and Energy Metabolismmentioning
confidence: 99%
“…2). Circulating fatty acid levels are elevated during ischemia (74,85,97), and it has been shown that high plasma fatty acid levels are detrimental to both the ischemic and the reperfused ischemic heart (53,86,88,103). During myocardial ischemia, AMPK is activated, which leads to the phosphorylation and inhibition of ACC (72,73), increased GLUT4 levels in the sarcolemmal membrane (142), and the activation of PFK-2 (73, 106, 108, 109).…”
Section: Regulation Of Myocardial Energy Utilizationmentioning
confidence: 99%